Evaluation of lubrication performance of crank pin bearing in a marine diesel engine - Suk Man Moon; Yong Joo Cho; Tae Wan Kim (Friction)
Abstract In this study, the lubrication performance of the crank pin bearing in a marine two–stroke diesel engine is evaluated to investigate the adhesional failure on the crank pin bearing. A numerical algorithm for the lubrication analysis considering motion analysis of the crank pin system is developed. The film pressure and thickness for three clearances and three lubricant temperatures are calculated. The results show that the lubricant temperature has a higher effect on film thickness than clearance. In terms of the film parameter, the operating condition that can result in solid–solid contact is investigated. We also suggest the desirable operating conditions of clearance and lubricant temperature to prevent the solid–solid contact.